Analiza przyczyn i konsekwencji upadków u chorych z zespołem Parkinsona = Analysis of the causes and consequences of falls in patients with Parkinson's syndrome - Katarzyna Strojek; Agnieszka Witkowska; Agnieszka Radzimińska; Urszula Kaźmierczak; Zuzanna Piekorz; Irena Bułatowicz; Aleksander Goch; Walery Zukow (Journal of Education, Health and Sport, 2015)
Strojek Katarzyna, Witkowska Agnieszka, Radzimińska Agnieszka, Kaźmierczak Urszula, Piekorz Zuzanna, Bułatowicz Irena, Goch Aleksander, Zukow Walery. Analiza przyczyn i konsekwencji upadków u chorych z zespołem Parkinsona = Analysis of the causes and consequences of falls in patients with Parkinson's syndrome. Journal of Education, Health and Sport. 2015;5(5):548-555. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.38788